Structural Behavior of Steel Reinforced Concrete Joint Under Flexural Loads - Mohammed M. Handhal; Ali W. Abdulghani; Montaqa M. Al-Haydary (Civil Engineering Journal, 2023)
This research investigates the behavior of RC beam column joints reinforced with steel sections. The study deals with the strengthening of RC joints by different steel sections. The investigation included a theoretical analysis through a performing of simulation of beam-column joints laced with steel sections by using FEA. Implementation of the parametric study included reinforcing the concrete beam with steel sections in many configurations. Shapes and length were the most variables in this study, and many shapes were used, such as I-section, box section, and plates, beside the concrete compressive strength variable. The most recent study revealed the possibility of the method to enhance the efficiency of the joint in resisting the loads while the offering many additional features such as higher ductility, stiffness, and energy absorption. The results showed that strengthening by the steel section enhanced the flexural strength of the joint, but these enhancements were to a certain limit due to the concrete strength limitation. The ultimate strength enhancement was 49%, which is considered a good index for the joint efficiency. The use of compressive strength in small amounts led to the enhancements being limited due to the weakness of the concrete. Strengthening the flexural side of the beam by adding a steel section requires stronger concrete to provide more contribution for the steel section to resist more flexural loads. The increase in the compressive strength of the concrete made the improvements reach their peaks. Strengthening by I-shaped and box steel sections showed that the enhancement due to the existence of the I section was greater than that of the box one. Doi: 10.28991/CEJ-2023-09-03-015 Full Text: PDF